Word Of Mouth To Mediate Consumer Knowledge And Religiosity Towards The Decison To Settle As Sharia Bank Clientele - Nasiruddin, Iqbal; Yayuk Sri Rahayu (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to investigate the impact of consumer knowledge and religiosity on individuals choosing to become clients of Sharia banks, with word of mouth serving as the mediating variable. Employing a quantitative approach and purposive sampling techniques, the research focused on 145 respondents, primarily students from Islamic universities in Malang, including State Islamic University Maulana Malik Ibrahim, Islamic University of Malang, and Muhammadiyah University of Malang, who were already clients of Sharia banks. Questionnaire data were distributed and collected via Google Forms. The findings indicated that consumer knowledge alone did not directly influence the decision to become a Sharia bank client; however, it significantly affected word of mouth. Similarly, religiosity demonstrated a comparable impact on word of mouth and the decision to settle as a Sharia bank client. Consumer knowledge significantly influenced the decision to settle as a clientele through the full mediation of word of mouth, whereas religiosity had a significant effect on the decision, partially mediated by word of mouth.